The Oral Pathology Related Articles Published in Iranian Journal of Pathology from 2006 to 2015 - Thorakkal Shamim (Iranian Society of Pathology, 2016)
Background: There is a paucity of information about the oral pathology related articles published in a pathology journal. This study aimed to audit the oral pathology related articles published in Iranian Journal of Pathology (Iran J Pathol)from 2006 to 2015. Methods: Bibliometric analysis of issues of Iran J Pathol from 2006 to 2015 was performed using web-based search.The articles published were analyzed for type of article and individual topic of oral pathology. The articles published were also checked for authorship trends. Results: Out of the total 49 published articles related to oral pathology, case reports (21) and original articles (18) contributed the major share. The highest number of oral pathology related articles was published in 2011, 2014 and 2015 with 8 articles each and the least published year was 2012 with 1 article. Among the oral pathology related articles published, spindle cell neoplasms (7) followed by salivary gland tumors (5), jaw tumors (4), oral granulomatous conditions (4), lymphomas (4), oral cancer (3) and odontogenic cysts (3) form the major attraction of the contributors. The largest numbers of published articles related to oral pathology were received from Tehran University of Medical Sciences; Tehran (7) followed by Mashhad University of Medical Sciences, Mashhad (6) and Shahid Beheshti University of Medical Sciences, Tehran (5). Conclusion: This paper may be considered as a baseline study for the bibliometric information regarding oral pathology related articles published in a pathology journal.